Bichectomia as a surgical option for aesthetic-functional harmony. A case report: Bichectomía como cirugía de eleccion en la búsqueda de la armonía estéticofuncional. Reporte de caso - Guerra Escorcia, Nicole; Espinosa Segura, Brian; Martínez Martínez, Adel; Díaz Caballero, Antonio (Gaceta Médica de Caracas, 2025)
Bichectomy is the partial surgical removal of an anatomical structure known as Bichat’s fat pad. This technique involves removing the buccal portion of the fat pad, which influences facial contour and can create a rounded, less aesthetically pleasing appearance in some patients. This case report presents a 26-year-old female patient who sought consultation at a public dental clinic due to concerns about facial asymmetry, requesting surgery for Bichat’s fat pad removal. The patient experienced no complications or risks during the surgical procedure, and the postoperative period progressed without incident. The procedure successfully met the patient’s expectations, achieving enhanced cheekbone definition and improved facial harmony. Based on this experience, bichectomy proves to be an efficient procedure that fulfills its aesthetic and functional objectives when carefully considering the anatomical relationships of the buccal fat pad during extraction. The procedure effectively improves facial aesthetic harmony and masticatory functionality, provided that proper surgical technique and anatomical considerations are maintained throughout the intervention.